Assessment of skeletal muscle mass in critically ill patients: considerations for the utility of computed tomography imaging and ultrasonography - Paris, Michael; Mourtzakis, Marina (Wolters Kluwer, 2016)
Purpose of review: Low muscularity and skeletal muscle atrophy are commonly exhibited in critically ill patients and have major implications on patient outcomes. Typically, in the ICU, body composition is assessed through anthropometrics or bioelectrical impedance analysis, but these modalities cannot specifically quantify skeletal muscle; thus, we evaluate the merits and challenges of using computed tomography (CT) and ultrasonography to specifically measure skeletal muscle in the ICU. Recent findings: CT-based cut points have been used to identify critically ill patients with low muscle mass, and low muscularity associates with poor clinical outcomes and function. Ultrasonography is emerging as a useful tool to quantify skeletal muscle loss and degradation in architecture, as well as prospectively track changes in these parameters over time. Rates of muscle atrophy and changes in muscle architecture has been quantified by ultrasonography and associated with poor clinical outcomes, but identification of critically ill patients with low muscularity is still in its infancy. Summary: CT imaging and ultrasonography require additional comprehensive validations against accurate measures of whole body muscle mass. As these validations begin to emerge, there will be a need to translate this knowledge into a simple tool that clinicians can apply as part of routine care.
Keywords: computed tomography; ultrasound; Body composition; skeletal muscle; critical care